The Evaluation of thermal, room acoustics and daylight performance of Old Indraputi Mosque in Aceh Besar, Indonesia / Laina Hilma Sari - Laina, Hilma Sari; Izziah, L. H.; Erna, Meutia; Zulfian, Zulfian (Universiti Teknologi MARA, Perak, 2019)
This paper aims at assessing the performance of thermal, room acoustics and daylight of the old Indrapuri mosque. Indrapuri mosque is located in Aceh Besar and built in the 12th century. The mosque is famous with the history of Aceh; therefore, it belongs to the cultural heritage object conserved by e government. After some decades, the facade has been maintained and conserved. However, some conservation steps were shifted from the principle ones such as using traditional techniques and materials. The data were collected using survey and mechanical measurement. The results show that some replacements cause some spatial discomforts such as higher indoor thermal performance. It is indicated in Olgyay’s bioclimatic chart which also shows that the air movement should be increased to reach the comfort zone. The mosque acoustics performance has slightly high background noise, while the sound pressure level and reverberation time still meet the standard. The daylight remains good. This is shown when there is no electrical light is switched on during the day including daytime prayer i.e. Zuhr (1 pm) and 'Ashr (4 pm).